CRE AI A Transnational Framework for Ethical AI Upskilling in the Creative Industries: A Network Learning Perspective - Miloshevski, Viktor; Hurkmans, Gert (Proceedings of the International Conference on Networked Learning, 2026)
The rapid integration of Artificial Intelligence (AI) into the creative sectors presents a paradigm shift, offering novel tools for artistic expression while simultaneously raising critical ethical concerns. This paper presents the CRE AI project, an Erasmus+ initiative designed to address the dual challenge of skills gaps and ethical literacy among creative professionals. We position the project’s intervention—a transnational, multilingual e-learning platform and community—within the theoretical framework of Networked Learning (NLEC, 2021; Ryberg et al., 2025). The paper argues that the project’s design inherently fosters the collaborative, relational, and technology-mediated learning processes central to networked learning. By creating digital spaces for connection, peer support, and critical dialogue around ethical AI practice among diverse adult learners and educators across Europe, the project moves beyond simple knowledge transmission. It actively cultivates a Community of Practice and a supportive learning network. Using a mixed-methods strategy, the project evaluates increases in learner competence, confidence, and ethical application. The expected results, including sustainable OER and a lasting support network for "ethical creatives," are framed as contributions to fostering equitable, human-centric, and networked professional learning ecosystems in the creative industries. We contend that the CRE AI model exemplifies how targeted educational interventions can leverage networked learning principles to empower creative professionals, ensuring technological advancement is coupled with collective social responsibility and critical digital agency.